New KEL*01M and KEL*02M alleles: structural modeling to assess the impact of amino acid changes. Issue 5 (20th March 2016) - Silvy, Monique; Callebaut, Isabelle; Filosa, Lugdivine; Granier, Thomas; Chiaroni, Jacques; Bailly, Pascal
Abstract : BACKGROUND: The KELL antigens are carried by the well‐folded and highly polymorphic glycoprotein KELL, belonging to the M13 family of metalloproteases. Anti‐KEL, particularly anti‐KEL1, are clinically significant. We retrospectively investigated genomic DNA from samples with uncertain KEL1 or KEL2 phenotype and identified six novel Kmod alleles. We then considered a model of the protein three‐dimensional (3D) structure to assess the impacts of the amino acid changes. STUDY DESIGN AND METHODS: The 19 exons of the KEL gene were polymerase chain reaction amplified and sequenced. Modeling was performed using the experimental 3D structure of human endothelin‐converting enzyme‐1 in the presence of the metabolite phosphoramidon. RESULTS: We identified four novel KEL*01M alleles with amino acid substitutions p.Arg447Trp, p.Gly641Arg, p.Ala645Val, and p.Gly703Arg found buried within helices of the ectodomain catalytic lobe. We also revealed one new KEL*02M allele with p.Gly263Glu in contact with solvent (water) located within the second lobe of the ectodomain. One sample with c.575G>C transversion (p.Arg192Pro) on a KEL*02 background showed a weakened reactivity for KEL1. According to our 3D modeling, these amino acid substitutions may have a profound impact on the protein structure. CONCLUSION: This study is especially interesting with regard to the description of four new KEL*01M alleles. Indeed, to date only two KEL*01M alleles have been described and our data suggest a nonnegligible incidence of KEL1 variants. Serologic KEL2‐negative results as well as any ambiguity implying either KEL1 or KEL2 in donors should always be confirmed by means of genotyping analysis and discrepancies between these methods require sequencing of KEL gene.